Tomography diagnostic of plasma radiated power on the spherical tokamak Globus-M - Sladkomedova, A. D.; Alekseev, A. G.; Bakharev, N. N.; Gusev, V. K.; Khromov, N. A.; Kurskiev, G. S.; Minaev, V. B.; Patrov, M. I.; Petrov, Yu. V.; Sakharov, N. V.; Shchegolev, P. B.; Solokha, V. V.; et al. (Review of scientific instruments, 2018)
A diagnostic system for plasma radiated power tomography on Globus-M was upgraded with a new linear array based on silicon photodiodes. The hardware of the diagnostic system based on a 256-channel tangential matrix array and a 24-channel linear array is described. The algorithm for 2D tomographic reconstruction of plasma emissivity is presented. It uses the Tikhonov regularization method and anisotropic diffusion functional as a side constraint. Simulated plasma emissivity profiles were used to test and assess the capabilities of the developed algorithm. Data analysis was carried out in ohmic and neutral beam heated discharges to demonstrate the performance of the tomography diagnostic in plasmas with different parameters. The presented results illustrate the proper functioning of the tomography system that allowed to reveal and study various plasma phenomena, including magnetohydrodynamic mode.